(untitled) - Haynes, Gary (Cambridge UK, 2002)
This history of the first people to settle in the New World starts with a summary of the archaeology of Clovis-fluted point-makers in North America.
Keywords: Paleo-Indians,Văn hóa Clovis,Clovis culture; North America